2010
DOI: 10.2737/nrs-gtr-62
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining America's urban trees and forests: a Forests on the Edge report

Abstract: Close to 80 percent of the U.S. population lives in urban areas and depends on the essential ecological, economic, and social benefi ts provided by urban trees and forests. However, the distribution of urban tree cover and the benefi ts of urban forests vary across the United States, as do the challenges of sustaining this important resource. As urban areas expand across the country, the importance of the benefi ts that urban forests provide, as well as the challenges to their conservation and maintenance, wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…Urban foresters typically focus on trees located along streets as well as in public parks and natural areas. However, since one of the main goals of urban forestry is to optimize forest benefits for society, urban foresters can also help guide the management of trees on private lands, which typically dominate the overall urban forest composition (Nowak et al 2010).…”
mentioning
confidence: 99%
“…Urban foresters typically focus on trees located along streets as well as in public parks and natural areas. However, since one of the main goals of urban forestry is to optimize forest benefits for society, urban foresters can also help guide the management of trees on private lands, which typically dominate the overall urban forest composition (Nowak et al 2010).…”
mentioning
confidence: 99%
“…We argue that promising financial potential provides incentives for local governments to utilize marginal and abandoned industrial lands to increase urban canopy coverage, and to adopt stricter tree management ordinances to boost the carbon storage capacity of public trees. Nowak et al (2010) noted that about one half of the sample in a recent survey of the United States cities with population of 30,000 or more indicated that expanding tree canopy is their goal and as much as 95% of them have even adopted some sort of tree management ordinance (City Policy Associates, 2008 However, some research results suggest that the long-term viability of urban forests as a source of carbon credit may be debatable. First, as Nowak et al, (2010) note that increasing tree coverage may increase the potential for storing additional carbon in urban tress, but the maximum tree coverage will entail additional risk and costs, such as wildlife risk along high density residential areas, human-wildlife conflict due to expanded habitat for birds and animal species, and water usage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, about 56% of the respondents had at least a portion of their forest resource recently inventoried. A similar survey of U.S. cities recently conducted by the United States Conference of Mayors suggested that as much as 55% of cities had a current inventory of urban tree canopy (Nowak et al, 2010). When asked if local governments were currently participating in any climate change initiatives, respondents identified a number of projects, including remodeling and construction of energy efficient buildings, using alternative fuel vehicles, capturing landfill methane, and planting trees.…”
Section: Seller's Surveymentioning
confidence: 99%
“…Concerning vegetation, this takes the shape of urban forestry and green architecture (Lehmann 2014). Urban forestry is the incorporation of trees in and around the urban community for the environmental, social, economic, and aesthetic benefits trees provide (Konijnendijk et al 2006;Nowak et al 2010). With respect to urban heat island mitigation, the benefits of forestry extend beyond impacting those whom inhabit the community to the environment of the community itself.…”
Section: Strategic Vegetationmentioning
confidence: 98%